Insect and legume-based protein sources to replace soybean cake in an organic broiler diet: Effects on growth performance and physical meat quality. Issue 1 (16th December 2015) - Leiber, F.; Gelencsér, T.; Stamer, A.; Amsler, Z.; Wohlfahrt, J.; Früh, B.; Maurer, V.
Abstract: Protein sources other than soybean for the diets of poultry are needed for agricultural systems in temperate regions to help avoid some negative social and ecological impacts of large-scale soybean imports from overseas. The aim of the present study was to test the suitability of alternative protein sources in diets for slow-growing organic broiler chicken. Four experimental broiler diets were tested against a commercial feed for organic broiler chicken fattening (control), containing 255 g kg −1 soybean cake. Each experimental diet was based on the control diet, but 130 g kg −1 of soybean cake was replaced with alternative feeds. The diet 'HermAlf' contained 78 g kg −1 Hermetia meal (dried larvae of the black soldier fly, Hermetia illucens ) and 52 g kg −1 alfalfa ( Medicago sativa ) meal. Diet 'HermPea' contained 78 g kg −1 Hermetia meal and 52 g kg −1 pea ( Pisum sativum ) groats. Diet 'AlfPea' contained 78 g kg −1 alfalfa meal and 52 g kg −1 pea groats. Diet 'PeaAlf' contained 78 g kg −1 pea groats and 52 g kg −1 alfalfa meal. Both diets containing Hermetia meal had the same amount of crude protein (CP) concentration as the control, while CP concentration was lower in diet AlfPea (by 2.7%) and in diet PeaAlf (by 3.5%) compared with the control. Over the course of the experiment, 15 broilers each (slow-growing Hubbard S757) were fattened with one of the five diets ad libitum from days 7 to 82. Additionally, all broilers received water and wheat grains ( Triticum aestivum ) ad libitum . Feed intake was measured by group. Daily gains, live weights, carcass weights and meat quality were analyzed individually. Compared with the control, feed intake, daily weight gain, carcass weights and feed efficiency were equivalent for all experimental diets. Regarding quality parameters, only cooking loss was increased with the HermPea diet compared with the control. The results indicate that the alternative feeds tested could replace part of the soybean products in broiler diets while achieving equivalent feed efficiency and product quality.